Radiation Interception and Use Efficiency Contributes to Higher Yields of Newer Maize Hybrids in Northeast China. (1st July 2015) - Zhao, Jin; Yang, Xiaoguang; Lin, Xiaomao; Sassenrath, Gretchen F.; Dai, Shuwei; Lv, Shuo; Chen, Xiaochao; Chen, Fanjun; Mi, Guohua
Abstract : A significant trend of decreasing solar radiation has been observed in Northeast China over the past six decades. Such a decline in solar radiation could negatively impact maize ( Zea mays L.) production. The improved cultivated hybrids may have adapted to these changes in solar radiation. In this study, four commonly cultivated maize hybrids in Northeast China were selected for a 2‐yr field study. Two hybrids were released in the 1970s and the other two were released in the 1990s. In comparison with the maize hybrids released in the 1970s, the maize hybrids released in the 1990s exhibited significant increases in both dry matter at maturity ( P < 0.05) and grain yields ( P < 0.05), although the harvest index (HI) showed no significant difference. The greater dry matter accumulation was primarily responsible for the yield increase observed in the 1990s' hybrids. The greater dry matter accumulation occurred primarily during the tasseling‐to‐maturity stage. Our results indicated significant improvements ( P < 0.05) in crop growth rate and radiation use efficiency (RUE) in 1990s' hybrids, particularly during the tasseling‐to‐maturity stage. Additionally, the net photosynthetic rate (NPR) of the ear‐leaf before 1200 h was also significantly improved in the 1990s' hybrids. The fraction of photosynthetically active radiation (PAR) interception on the third leaf above the ear‐leaf was increased during the tasseling‐to‐maturity stage and significantly correlated with maize grain yields ( P < 0.01), indicating that the increase in the fraction of PAR interception at this layer contributed to the higher grain yield in the 1990s hybrids.